PENGARUH COVID 19 BAGI PENDIDIKAN ANAK USIA DINI DI KAITKAN DENGAN HADIST MENUNTUT ILMU DI TK ISLAM NAJMAH RUGAYAH DARUS MEDAN HELVETIA - Abdul Muthalib; Juliana; Diana Wijayanti; Puput Syahputri (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2021)
This research discusses the obstruction of activites in the world of early childhood education due to the covid 19 pandemic. The study aims to determine the extent of the Islamic kindergarten education institution Najmah Rugayah Darus, and it is associated with the tradition of the prophet Muhammad about the obligation to study. Data collection was carried out by means of research observation, interviewing school principals, teachers and seeing data on the number of students in school notebooks (documents) of the Islamic kindergarten education institution Najmah Rugayah Darus, the results of the research and interviews are described,and analyzed. The Islamic kindergarten education institution Najmah Rugayah Darus changes the teaching and learning proces, learning model even although due to covid 19the number of students has decreased. Hopefully the policies taken by the Islamic kindergarten education institution Najmah Rugayah Darus can be emulated by other early childhood education institutions.